Johann George Schreiber’s Atlas selectus: new findings - Paprotny Zbigniew (Polish Cartographical Review)
This update to the earlier paper on Schreiber’s Atlas selectus (Paprotny, 2020) presents new findings supplementing and specifying information about the Atlas, its editions, dating, and maps. Discussed are recently discovered prototype versions of the Atlas which preceded series of “canonical” editions, and status of post-1795 copies. An updated list of 32 Atlas editions known today has been compiled, together with catalogue of its maps, identifying their occurrence in the individual editions. Corrections to Jäger’s catalogue of maps from Schreiber’s workshop are proposed.